Collagierte Realitätssplitter - Wolfgang Bunzel (Recherches Germaniques)
Karl Henckells Berliner Abendbild and Arno Holz’ Nicht „antiker Form sich nähernd“ belong to those poems of Naturalism which can claim a permanent place in the changing history of poetry. Berliner Abendbild exemplarily proves the discovery of the city as a literary topic but also as a new space of experience in German Naturalism. But what is innovative in this text is especially the way in which Henckell collages scraps of conversation and thereby delivers something like a micro-sonogram of the city. On the other hand Holz transposes in Nicht “antiker Form sich nähernd” the coexistence of heterogeneous statements, corresponding to the journalistic mode of presentation, to poetry and thereby finds not only a form to express the contradictions of the modern world but also proves a montage-like technique of representation which anticipates the future of literature.urban poetry, critique of ideology, poetic collage, naturalism, reflection on language